Application of differentiated learning using a problem-based learning model to improve students' mathematics learning outcomes - Muslim, Rizky Hidayatul; Febrian, Ferbrian; Yazid, Ibnu (IAIN Palangka Raya, 2024)
This study aims to improve students' mathematics learning outcomes by combining problem-based learning strategies with differentiated teaching. The action research was conducted using the Kemmis and McTaggart model in two cycles, each consisting of planning, implementation, observation, and reflection stages. The study involved 47 students from SMAN 2 Tanjungpinang, with data collected through assessment. The results showed a significant improvement in students' mathematics skills: the pre-cycle classical learning completeness rate of 29.78% increased to 57.44% in cycle one and further to 82.97% in cycle 2. Thus, the application of differentiated teaching within a problem-based learning framework improves students' mathematics learning outcomes.